AKUNTABILITAS DI DINAS PENDIDIKAN PROVINSI BANTEN - Kandung Sapto Nugroho (Universitas Sultan Ageng Tirtayasa, 2010)
One of the goals of accountability dalah application of the concept of service where it is a consciousness in order to restore the dignity of people in the region, providing educational opportunities in order to improve the quality of political democracy in the region, improving the efficiency of local public services and public services as well as closer to the community, increased acceleration of development in the region, reducing regional imbalance in development, is also expected that the implementation of the governing how good (good governance) which in the end is for the welfare of society. Formulation of the problem in this study that is how the application of the principles of good governance in Banten Provincial Government Education Department? This research used descriptive survey with quantitative research approaches. Objectives of this research is all education stakeholders in the province of Banten in this case the whole range of educational bureaucracy, all layers of civil society, and all employers who interact with the world of education. Mechanical determination of sample taken is quota sampling technique, the total sample will amount to 90 respondents. The conclusion of this study that the rate of application of the principle of good governance in the Department of Education when viewed on the principle of voice and accountability levels reached 46.75 application included in the category of poor governance.